polymer grafted TEMPO as a mediator for cellulose oxidation - Fu, Qiang (My University, 2017)
TEMPO-mediated oxidation is a widely used approach to introduce aldehyde and carboxyl groups on cellulose. In the conventional TEMPO-mediated oxidation, the mediator TEMPO is a small molecule. Previous research in our group advanced TEMPO-mediated oxidation by grafting TEMPO onto high molecular weight poly(acrylic acid) and polyvinylamine. The polymer grafted TEMPO-mediated oxidation required less TEMPO and had a lower environmental impact. This thesis describes new insights into the role of polymer grafted TEMPO as mediator for cellulose oxidation. The redox-activity of grafted TEMPO was analyzed by electrochemical techniques and the resulting aldehyde densities on cellulose surfaces, produced by polymer grafted TEMPO, were determined with a fluorescence-labeling method. The properties of polymer grafted TEMPO solutions are essential to understanding the role of grafted TEMPO as the oxidation mediator. TEMPO substitution compacted both the conformation of poly(acrylic acid) and polyvinylamine due to the lower hydrophilicity of the TEMPO substituents. Poly(acrylic acid-g-TEMPO) (PAA-T) solutions phase separated over the pH range 2-4, whereas at lower and higher pH the polymer was water-soluble. The phase separation at low pH was proposed to be the combined result of the hydrophobic contributions of the TEMPO moieties and electrostatic interactions between the acid-induced cationic TEMPO species and the anionic ionized carboxyl groups. Polyvinylamine-g-TEMPO (PVAm-T) was water-soluble over a larger pH range (pH 1-9) due to the ionization of the amine groups. Both the PAA-T and PVAm-T were slightly surface active. Multilayer films composed of PVAm-T and poly(styrene sulfonate) were stable and redox-active. Charge transport in the redox multilayer films was realized through TEMPO-to-TEMPO electron hopping between neighboring TEMPO moieties. Only 20-30% of TEMPO moieties were redox-active, reflecting the requirement that TEMPO moieties must be closer than ~ 0.6 nm for electron hopping to occur. The redox multilayer films displayed significant interpenetration of layers. The ability of PVAm-T to spontaneously adsorb onto negatively charged surfaces in aqueous solutions provides an easy route to TEMPO-rich surfaces for other applications. Specific attention was focused on the role of PVAm-T as mediator for cellulose oxidation in the presence of laccase. Positively charged PVAm-T formed colloidal complexes with negatively charged laccase. The behaviors of PVAm-T/laccase mixtures displayed the classic features of polyelectrolyte complexes formed between oppositely charged polyelectrolytes. For the first time, electrochemical quartz crystal microbalance with dissipation (EQCM-D) measurements were used to characterize the redox properties of the adsorbed PVAm-T/laccase complexes. The role of PVAm-T as mediator for cellulose oxidation depended upon TEMPO-to-TEMPO electron transfer within PVAm-T/laccase colloidal complexes. The aldehyde density on oxidized cellulose surfaces scaled with the square root of surface molar density of redox-active TEMPOs which, in turn, was a linear function of TEMPO degree of substitution in PVAm-T. As a result, the aldehyde density on cellulose surfaces, generated by PVAm-T/laccase oxidation, can be controlled by varying the TEMPO degree of substitution in PVAm-T.
Keywords: TEMPO; cellulose oxidation; electron tranfer; EQCM-D